THE TIME INDICATORS OF PERFORMANCE BY ORTHOPEDIC SPECIALISTS COMPLEX PROTOCOL OF MANUFACTURING COMPLETE CONDITIONALLY-REMOVABLE PROSTHESIS RELYING ON IMPLANTS - E.V. Diiev; V.A. Labunets; S.A. Schneider; T.V. Diieva (Український стоматологічний альманах)
Full conditionally removable dentures relying on dental implants are widely used in medical practice in Ukraine and are made either by injection basing on plastic burnout abutments, either by gluing basing on the abutment with the platform for bonding. Supports for such structures intraosseous implants are used in an amount of 2-6 units in the lower jaw and 4-8 units on upper one. Prosthesis is made both in immediate loading protocol, and in the protocol stitched in load time. In case, this type of denture still does not have, in our country, a full legal status for being applied.